Outcome Measures for Effective Teamwork in Inpatient Care Final Report - Sorbero, Melony E. (RAND Corporation, 2008)
Addresses one step in the process of moving from teamwork training to teamwork practices that improve outcomes of care: identifying outcomes that are most likely to be affected as teamwork practices improve in an implementing organization. Discusses a literature search, methods for selecting and testing candidate measures, measures highly rated by clinical experts, and results of measure testing on administrative data of the DoD health system.